Where are the most vulnerable areas to climate induced insecurities and risks in Nigeria? - Achicanoy Estrella, Harold Armando; Ramírez Villegas, Julián Armando; Mendez Alzate, Andres Camilo; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Nigeria, using spatial hotspot analysis. The findings show that areas of high conflict and harsh climate interactions co-occurred with hotspots of socio-economic vulnerabilities where migration and inequality issues are present (local authorities of Kware and Wurno), low productivity (northern limits of Marte and Ngala) and inequality and low productivity (Jere and Konduga local authorities).